Moderate multidimensional poverty index: Paving the way out of poverty - Alkire, S; Kovesdi, F; Scheja, E; Vollmer, F (Oxford Poverty and Human Development Initiative, 2020)
This paper introduces a trial Moderate Multidimensional Poverty Index (MMPI) that provides a meaningful superset of existing global multidimensional poverty indices. Eradicating poverty in all its forms everywhere requires indicators that measure sustainable pathways out of poverty, not only the absence of extreme deprivation. The MMPI increases the deprivation cutoff of nine of the ten indicators of the global Multidimensional Poverty Index (gMPI) to reflect moderate rather than acute levels of multidimensional poverty, in line with the ambitions outlined in the Sustainable Development Goals (SDGs). The MMPI is constructed as a superset to the global MPI maintaining the three dimensions of health, education and living standards, but adjusting nine of the indicators to reflect a meaningful change in the level of ambition. The trial MMPI is data-constrained, but provides a methodology and discusses potential indicators for an MMPI that would: i) be globally comparable across countries at all income levels, ii) align the indicators with the higher standards for development as defined in the Agenda 2030, and iii) allow us to study some aspects of intrahousehold deprivation. The trial MMPI is illustrated empirically using nationally representative household surveys from Thailand, Iraq, Tanzania, Serbia, Guatemala, and Bangladesh. The empirical results in the six countries show the added value of having three layered measures of destitution, acute poverty, and moderate poverty. The MMPI aligns reasonably well with the established monetary poverty levels in lower middle-income countries ($3.2 / day) and in upper middle-income countries ($5.5/day), yet with some informative differences. The results demonstrate that the MMPI is feasible, has desirable properties as a global poverty index, and allows to unearth thus far hidden aspects in poverty measurement, such as intrahousehold deprivations in education. Still, challenges remain in terms of data availability for certain indicators and a study across additional countries is required before an MMPI structure can be finalized.